Prevalence of Low Back Pain among School-Aged Children between 10 and 12 Years - Josep Vidal-Conti (MDPI AG, 2021)
Low back pain (LBP) is one of the biggest health problems worldwide that often begins during childhood. The existence of a previous episode of LBP is a premonitory sign of future back pain problems, therefore, prevention among youth will be essential. The main objective of the study was to determine the lifetime, point, and 7-day prevalence of LBP in children. This cross-sectional study evaluated 849 participants (47.1 boys and 52.9% girls) aged 10–12 from 10 primary schools using a self-administered questionnaire. The results demonstrated a lifetime prevalence of LBP of 73.6%, a last 7-days prevalence of 21.2%, and a point prevalence of 9.66%. LBP intensity reported in a Visual Analogue Scale (VAS) was 3.37 (SD 2.02). Chi-square analysis identified a significant difference between boys and girls in LBP lifetime prevalence (p < 0.001), 7-day prevalence (p = 0.035), and point prevalence (p = 0.014). The Student’s t-test in pain intensity showed the same differences (p = 0.007). Studies on LBP prevalence in young primary school students are scarce. Therefore, future studies investigating the prevention of LBP should focus on school interventions since schools are the most suitable institutions to participate in back pain prevention and health promotion.